The role of oxidative stress on the pathophysiology of metabolic syndrome - Francisqueti, Fabiane Valentini [UNESP]; Chiaverini, Lidiana Camargo Talon [UNESP]; Dos Santos, Klinsmann Carolo [UNESP]; Minatel, Igor Otávio [UNESP]; Ronchi, Carolina Berchieri [UNESP]; Ferron, Artur Junio Togneri [UNESP]; Ferreira, Ana Lúcia A. [UNESP]; Corrêa, Camila Renata [UNESP] (FapUNIFESP (SciELO), 2017)
Metabolic syndrome (MetS) has a high prevalence around the world. Considering the components used to classify MetS, it is clear that it is closely related to obesity. These two conditions begin with an increase in abdominal adipose tissue, which is metabolically more active, containing a greater amount of resident macrophages compared to other fat deposits. Abdominal adiposity promotes in?ammation and oxidative stress, which are precursors of various complications involving MetS components, namely insulin resistance, hypertension and hyperlipidemia. One way to block the effects of oxidative stress would be through the antioxidant defense system, which offsets the excess free radicals. It is known that individuals with metabolic syndrome and obesity have high consumption of fats and sugars originated from processed foods containing high levels of sodium as well as low intake of fruits and vegetables, thus maintaining a state of oxidative stress, that can speed up the onset of MetS. Healthy eating habits could prevent or delay MetS by adding antioxidant-rich foods into the diet.
Keywords: Metabolic syndrome; Obesity; Oxidative stress